2018
DOI: 10.1007/978-3-319-76735-2_15
|View full text |Cite
|
Sign up to set email alerts
|

Models of Disease

Abstract: Osteochondral (OC) lesions are a major cause of chronic musculoskeletal pain and functional disability, which reduces the quality of life of the patients and entails high costs to the society. Currently, there are no effective treatments, so in vitro and in vivo disease models are critically important to obtain knowledge about the causes and to develop effective treatments for OC injuries. In vitro models are essential to clarify the causes of the disease and the subsequent design of the first barrier to test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 117 publications
0
3
0
Order By: Relevance
“…For these reasons, in vitro 3D models have become important tools in the development and testing of potential treatments and strategies to improve the regeneration process of bone, cartilage, or osteochondral interphase. On the one hand, they are useful for studying and improving the integration of the newly formed tissue with the surrounding environment [95]; on the other hand, they are considered valid 3D models for bone disease studies [96]. Indeed, 3D composite bone tissue scaffolds with both mechanical stability and drug-delivery functionality are employed to study the drug-delivery properties of statins, biocompatibility, alkaline phosphatase activity, and osteoblasts activity in vitro for the treatment of osteoporosis [97].…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, in vitro 3D models have become important tools in the development and testing of potential treatments and strategies to improve the regeneration process of bone, cartilage, or osteochondral interphase. On the one hand, they are useful for studying and improving the integration of the newly formed tissue with the surrounding environment [95]; on the other hand, they are considered valid 3D models for bone disease studies [96]. Indeed, 3D composite bone tissue scaffolds with both mechanical stability and drug-delivery functionality are employed to study the drug-delivery properties of statins, biocompatibility, alkaline phosphatase activity, and osteoblasts activity in vitro for the treatment of osteoporosis [97].…”
Section: Applicationsmentioning
confidence: 99%
“…Osteoarthritis studies, showed complex 3D models to reproduce the osteochondral interface, involving elements of the cartilage component and the well-vascularised cartilage-to-bone transition zone [99]. These engineered constructs are multiphasic structures with a particular rigid and porous section containing osteoblasts and endothelial cells, corresponding to the subchondral bone, a hydrated and viscoelastic section containing chondrocytes to reproduce the cartilaginous region [96]. The triphasic models are the ideal system for studying the complex cellular interactions in health or disease conditions affecting this area [100,101].…”
Section: Applicationsmentioning
confidence: 99%
“…Additive manufacturing methods allowed the development of 3D biomimetic and customized scaffolds that support cell viability and functions [ 210 ]. Among 3D printing approaches, electrospinning gained considerable attention as it generates structures with the submicron resolution by reproducing specific surface topography, which is another critical aspect to consider when studying cell behavior [ 211 , 212 , 213 ]. When referring to 3D models with scaffolds, their selection covers great importance, since findings vary greatly based on their nature and architecture.…”
Section: Conclusion and Future Research Outlookmentioning
confidence: 99%